Verbal and non-verbal methods of activation of cognitive behavior of educational applicants in the process of learning foreign languages - Nalyvaiko, О.; Nuralieva, L.; Syvolotska, L. (Scientific notes of the pedagogical department, 2021)
The article considers the analysis of the use of verbal and non-verbal methods in the process of learning foreign languages. The relevance of this research is connected to the fact that the learning of foreign languages in the modern world is becoming advanced and progressive, so there is an urgent need to study the effectiveness of methods of activation of students` cognitive activity. The article highlighted such concepts as "verbal methods", "non-verbal methods", "interactive technologies of learning foreign languages", "The Silent Way", "the 25th frame effect" and "Schechter`s method", and also considered the features of various technologies and their effectiveness. This article highlights the results of a survey among students of the Faculty of Foreign Languages, V.N. Karazin Kharkiv National University, in which they had to answer twelve questions about the relevance of using the methods presented in the article and their attitude to them. Students shared their own experience and expressed their view on the feasibility of their use in the future in their professional activity. Based on the results of the survey, the authors of the research highlighted the most important issues regarding the use of interactive technologies in the process of learning foreign languages.